Inhibition by various substances of oedema formation in the hind-paw of the rat induced by 5-hydroxytryptamine, histamine, dextran, eggwhite and compound 48/80 - Parratt, J. R. (1958)
Of the substances studied for their inhibitory action of the oedema formation in the hind-paw of the rat, the most active was a new derivative of phenothiazine, related to chlorpromazine. It is methotrimeprazine {10-(3-dimethylamino-2-methylpropyl)-2-methoxyphenothiazine; 7044 RP}. This substance possesses potent antihistamine and anti-5-hydroxytryptamine properties, and doses of 0.25 mg./kg. inhibited the blueing and swelling of the foot after injections of histamine, 5-hydroxytryptamine, eggwhite, dextran or compound 48/80 into the feet of rats with sulphan blue (Evan's blue) dye in their circulation. The results indicate that both histamine and 5-hydroxytryptamine play rôles in increasing capillary permeability in the rat.